A high-voltage rechargeable magnesium-sodium hybrid battery. (April 2017) - Li, Yifei; An, Qinyou; Cheng, Yingwen; Liang, Yanliang; Ren, Yang; Sun, Cheng-Jun; Dong, Hui; Tang, Zhongjia; Li, Guosheng; Yao, Yan
Abstract: Growing global demand of safe and low-cost energy storage technology triggers strong interests in novel battery concepts beyond state-of-art Li-ion batteries. Here we report a high-voltage rechargeable Mg–Na hybrid battery featuring dendrite-free deposition of Mg anode and Na-intercalation cathode as a low-cost and safe alternative to Li-ion batteries for large-scale energy storage. A prototype device using a Na3 V2 (PO4 )3 cathode, a Mg anode, and a Mg–Na dual salt electrolyte exhibits the highest voltage (2.60 V vs. Mg) and best rate performance (86% capacity retention at 10C rate) among reported hybrid batteries. Synchrotron radiation-based X-ray absorption near edge structure (XANES), atomic-pair distribution function (PDF), and high-resolution X-ray diffraction (HRXRD) studies reveal the chemical environment and structural change of Na3 V2 (PO4 )3 cathode during the Na ion insertion/deinsertion process. XANES study shows a clear reversible shift of vanadium K-edge and HRXRD and PDF studies reveal a reversible two-phase transformation and V–O bond length change during cycling. The energy density of the hybrid cell could be further improved by developing electrolytes with a higher salt concentration and wider electrochemical window. This work represents a significant step forward for practical safe and low-cost hybrid batteries. Graphical abstract: Highlights: A hybrid Mg–Na battery with high working voltage of 2.6 V and excellent rate capability. A hybrid battery uses Mg anode, Na3 V2 (PO4 )3 cathode, and a dual salt non-nucleophilic Mg–Na electrolyte. Synchrotron radiation X-ray techniques reveal reversible phase transformation and various bonding length change.